‘Deep Deltoid Paradox Sign’ - Anterior Talofibular Ligament Laxity Prevents Development of Deep Deltoid Ligament Laxity in the Presence of Unstable Planus - A Cadaveric Study - Zhikai Li BA; Zhiheng Li; Gavin Jarvis MA(Cantab) MA PhD VetMB FHEA MRCVS; Stephanie Potten MB BChir; Cecilia Brassett MB BChir MChir FRCS FAS SFHEA; Chandra Pasapula MBBS BSc MRCS FRCS Orth (Foot & Ankle Orthopaedics)
Category: Hindfoot; Sports Introduction/Purpose: Adult Acquired Flatfoot Deformity (AAFD)/Progressive collapsing foot deformity (PCFD) starts with failure of the medial longitudinal arch. Determining which feet progress to anteromedial instability of the tibiotalar joint, prior to complete deltoid ligament rupture, is not fully understood. We have observed clinically that, in the presence of anterior talofibular ligament (ATFL) laxity, deep deltoid ligament (DD) laxity and anteromedial ankle instability does not develop (indicated by a negative neutral heel external rotation test/anteromedial drawer test). To date, the protective effect that ATFL rupture/laxity (the most common foot ligament injury) has on preventing DD laxity and anteromedial ankle instability developing in AAFD/PCFD has not been investigated. This understanding is crucial for accurate staging, treatment, and prognosis of both AAFD/PCFD and ATFL repairs. Methods: Unstable planus was induced in 12 cadaveric feet from 6 donors by complete sectioning of the plantar fascia, spring ligament and the plantar 1st tarsometatarsal joint. Paired feet were randomly assigned to having ATFL sectioned or ATFL intact. Feet underwent cyclic loading (2000 cycles) on a custom mounted jig and photos were taken with positional markers on the medial malleolus, fibula, and the talus before and after antero-posterior force application. ImageJ quantified anteromedial and anterolateral ankle joint displacement to reflect DD and ATFL laxity respectively. Results: In ATFL-intact feet, anteromedial displacement increased by 3.46 ± 0.41 µm/cycle (mean ± SD; P = 0.000005; two-tailed, one-sample t-test). In ATFL-sectioned feet, displacement increased 0.61 ± 0.66 µm/cycle (p = 0.072), an 82% reduction in DDL laxity development (P = 0.00006; two-tailed, paired t-test). There was minimal cycle-induced change in anterolateral displacement (ATFL-intact: 0.50 ± 0.50 µm/cycle (p = 0.06); ATFL-sectioned: -0.04 ± 0.90 µm/cycle (p = 0.17). However, absolute anterolateral displacement increased in ATFL-sectioned feet by 7.40 ± 0.12 mm (p = 0.00002). Conclusion: These findings corroborate our clinical findings; in AAFD/PCFD, feet with ATFL laxity paradoxically do not develop DD instability (negative heel external test and anteromedial draw test), which we ascribe the ‘deep deltoid paradox sign’. This phenomenon has significant implications in determining which feet progress to DD laxity in AAFD/PCFD and ultimately DD rupture. Furthermore, surgical management of ATFL ruptures may require patient counselling regarding the development of DD laxity after ATFL repair if AAFD/PCFD is also present. Finally, we propose putative mechanisms based on differential axes of talar rotation and navicular abduction during stance, straining DD when ATFL is intact.